(untitled) (Praxis Educativa, 2020)
This paper analyzes the curricular transformations of the Adult Secondary Education (ASE) in Argentina, from 1968 to the present. A documentary analysis of (N = 32) official texts provided by the Ministry of Education and an inductive characterization is carried out, allowing the identification and description of four stages characterized by strong political, social and economic changes. Each stage describes the ESA’s institutional objectives, the target population, the social and economic context, and its differences with other stages. The results indicate that at the beginning (stage 1), ASE was proposed to develop comprehensive adult education, based on the analysis of the adult students’ needs. Curricular transformations, as a result of laws such as state reform and the transfer of education services to jurisdictions and the National Education Law, led the ASE to assume new responsibilities away from the purposes which it was created for.